Severe acute respiratory syndrome coronavirus 2 antibody prevalence in adult patients with short bowel syndrome—A German multicenter cross‐sectional study. Issue 6 (27th June 2022) - Blüthner, Elisabeth; Pape, Ulrich‐Frank; Blumenstein, Irina; Wichmann, Jeanette; Tacke, Frank; Moosburner, Simon
Abstract: Background: Not all patients suffer from a severe course of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, demanding a definition of groups at risk. Short bowel syndrome (SBS) has been assumed to be a risk factor, because of the complexity of disease, the need for interdisciplinary care, and frequent contact with caretakers. We aimed to establish data on the course of infection and prevalence of SARS‐CoV‐2 seropositivity in SBS patients in Germany. Methods: From January 2021 until January 2022 a total of 119 patients from three different tertiary care centers with SBS were included. All patients received an antibody test against the nucleocapsid (N) antigen and were asked to fill out a questionnaire, which included frequency of contact with medical personnel, risk behavior and worries. Results: Sixty‐seven percent of SBS patients received parenteral nutrition with a median of 6 days per week. The seroprevalence of SARS‐CoV‐2 antibodies was 7.6% ( n  = 9). Seven patients with positive antibodies had coronavirus disease 2019 (COVID‐19) with a mild course. None of the patients were hospitalized or needed further treatment. There was no difference in willingness to take risks in SARS‐CoV‐2 antibody–positive and –negative patients ( P  = 0.61). Patients were predominantly worried about the economy (61%) and transmitting COVID‐19 (52%), less frequent (26%) about receiving insufficient medical treatment. Conclusion: These are the first clinical results concerning SARS‐CoV‐2 seropositivity and COVID‐19 disease in patients with SBS. The seropositivity is comparable to national data, which we attribute to increased risk awareness and avoidance. Further studies are warranted to investigate effects of COVID‐19 infection in SBS patients.